ANALYSIS OF THE SELF-REPORTED PHYSICAL ACTIVITY QUESTIONNAIRES INDICATORS - Fernate, Andra; Vazne, Zermena; Levskojs, Andrejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
“Global action plan on physical activity 2018–2030” emphasizes the need for weekly moderate physical activity for ensuring human health. Physical activity can be measured by a variety of objective and subjective methods, but one of the prerequisites for understanding the connection between active lifestyle and health certainty that the measuring instrument measures the feature for which it has been created and that it can be used in many countries. The goal of the research is to determine the correlations between measurement properties of fitness club clients’ self-reported physical activity indicators in the Global Physical Activity Questionnaire (GPAQ), International Physical Activity Questionnaire (IPAQ), European Health Interview Survey-Physical Activity Questionnaire (EHIS-PAQ), and to evaluate their concurrent validity. Methods: participants (volunteers) were 70 fitness club visitors (age 18-79). This research is preparative part for the further research of the project “European Physical Activity and Sports Monitoring System (EUPASMOS)”. The type, involvement and amount of physical activity was determined by the GPAQ, IPAQ and EHIS-PAQ adapted into Latvian. The research results showed that questionnaires allowed to determine the respondents’ physical activity indicators in and out of fitness club activities. Statistically significant correlations were determined between indicators obtained in all physical activity questionnaires applied in the research (p<0.05). This confirms that all three physical activity determination questionnaires can be used for physical activity research in Latvian environment.